(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Associations the bondage in which Indian society prevails. Githa Hariharan being an Indian females’ writer has authored short stories in addition to numerous novels. In all the novels of her, she deals with the theme of social, political issues. Githa Hariharan’s novels focus on feminist components and the’ The Ghosts of Vasu Master’ isn’t different from this. Nevertheless, Githa Hariharan portrays the marginalize females in Indian society. The girly ghosts include him the grandmother, and mother actress Rita Mona is boyhood fancy. Vasu Master does not live just in the present through his past also haunts him. He attempts to realize his existing. The novel is about wellbeing on all the levels body, mind, and soul.